(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
This study was carried out in the Department of Physiology and Pharmacology at Hajee Mohammad Danesh Science and Technology University to evaluate the effect of ipil ipil and calcium supplementation on egg production and live body weight of Japanese quail. Forty two days old “Japanese Quail” were divided into four groups (n=10 birds in each group). Group T0 was considered as control, fed only with commercial layer ration. Group T1 was additionally supplemented with 2 g grinded ipil ipil leaves, Group T2 with 2 g Dietary Ca sources and Group T3with 2 g grinded ipil ipil leaves with 2 g dietary Ca sources per kg feed. Observations were recorded for growth performance, egg production and egg quality of Japanese quail. Body weight (g) was increased significantly (p<0.05) in all treated groups in compared to control and best gain was recorded in combined action of ipil ipil and dietary Ca sources supplemented groups (155.6±2.59). In all treatment groups there were significantly increased in egg production, compare to control group. Best result was found in combination of ipil ipil and dietary calcium supplementation. The present study reveals that combine supplementation of ipil ipil and dietary Ca sources gives better effects over other groups in respect to growth performance, egg production and egg quality without any health hazard of Japanese quail. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 72-77